Politics, Ethnicity, and the Mission of the University: The Kenyan Example - Otieno, Weycliffe (International Higher Education, 2008)
The vulnerability of the education sector to the risks of political instability became clearly evident during the flare-up of violence following the disputed 2007 presidential elections in Kenya. Whereas universities especially in the developing world have often been seen as breeding grounds for radical political ideas and student activism, the post-election violence in Kenya directly affected university education, on a scale no other event has in the country's history. And, for the first time, the crisis facing education generally, and higher education specifically, showed clear ethnic manifestations.